TOURIST DESTINATION PLOVDIV - SPATIAL DIFFERENCES OF BULGARIAN TOURISM IN A PANDEMIC CONTEXT - Grigorova, Zlatka (Horizons - International Scientific Journal, 2021)
The development of the pandemic and the travel restrictions around the world are leading to the collapse of the tourism industry. Tourism is an important sector of the Bulgarian economy and Plovdiv. The purpose of this article is to analyze the impact of the pandemic on the Bulgarian tourism, taking into account its severity in the tourist destination Plovdiv. Statistical analyzes of the official statistics of tourism in Plovdiv before and during the pandemic have been performed. The increase in the number of infected in the country in early autumn has lead to restrictive measures and unpredictable consequences for the tourist season. The first year of the coronavirus has severely damagedthe tourism and consumer perceptions of safe travel. Conclusions were formulated on the socioeconomic consequences of the spread of the coronavirus pandemic for the regional markets of Bulgaria and destination Plovdiv.